2017
DOI: 10.1371/journal.pone.0186982
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5: A novel regulator of Hepatitis B virus replication and an arginine methylase of HBV core

Abstract: In mammals, protein arginine methyltransferase 5, PRMT5, is the main type II enzyme responsible for the majority of symmetric dimethylarginine formation in polypeptides. Recent study reported that PRMT5 restricts Hepatitis B virus (HBV) replication through epigenetic repression of HBV DNA transcription and interference with encapsidation of pregenomic RNA. Here we demonstrate that PRMT5 interacts with the HBV core (HBc) protein and dimethylates arginine residues within the arginine-rich domain (ARD) of the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 69 publications
1
48
0
Order By: Relevance
“…It is worth noting that residue M66 is located in helix 3 adjacent to the hinge region between helix 4a and helix 4b, which is bounded by residues T91 and K96. K96 is highly conserved across genotypes A, B, C, and D, is a key ubiquitination site involved in interactions with the surface antigen, and it appears to be involved in conformational changes between RNA-and DNA-containing capsids and therefore capsid maturation and nucleocytoplasmic trafficking [56][57][58]. Notably, this region of the sequence is also very different in the core antigen of the non-enveloped fish viruses (see section on phylogeny).…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…It is worth noting that residue M66 is located in helix 3 adjacent to the hinge region between helix 4a and helix 4b, which is bounded by residues T91 and K96. K96 is highly conserved across genotypes A, B, C, and D, is a key ubiquitination site involved in interactions with the surface antigen, and it appears to be involved in conformational changes between RNA-and DNA-containing capsids and therefore capsid maturation and nucleocytoplasmic trafficking [56][57][58]. Notably, this region of the sequence is also very different in the core antigen of the non-enveloped fish viruses (see section on phylogeny).…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…To probe for cell lysis, the supernatants of transfected cells were assayed for LDH activity (n ϭ 2). ylated, core species (27) and/or the precore protein. The precore protein is identical to core, save for its N-terminal ER signal sequence, composed of 29 residues, that directs precore to the ER, where 19 amino acids are cleaved off from the N terminus (10).…”
Section: Impacts Of Atg5 Atg12mentioning
confidence: 99%
“…Moreover, the interaction between PRMT5 and HBc was also demonstrated by CoIP assay in Huh7 cells ( Zhang et al, 2017 ). Several months later, a group from the Czech Republic showed that PRMT5 not only interacts with HBc, but that PRMT3 also weakly binds with HBc by GST pull-down assay from HEK293T cells ( Lubyova et al, 2017 ). They also found that HBc is methylated on its arginine residues at the C-terminal, with the R150 and R156 methylated sites being detected by mass spectrometry ( Lubyova et al, 2017 ).…”
Section: The Role Of Methylation In the Regulation Of Hbv Life Cyclementioning
confidence: 99%
“…Several months later, a group from the Czech Republic showed that PRMT5 not only interacts with HBc, but that PRMT3 also weakly binds with HBc by GST pull-down assay from HEK293T cells ( Lubyova et al, 2017 ). They also found that HBc is methylated on its arginine residues at the C-terminal, with the R150 and R156 methylated sites being detected by mass spectrometry ( Lubyova et al, 2017 ). The potential effect of arginine methylation in HBc is referred to as a regulator for controlling HBc binding to cellular factors, which participate in HBc shuttling between the nucleus and cytoplasm ( Lubyova et al, 2017 ).…”
Section: The Role Of Methylation In the Regulation Of Hbv Life Cyclementioning
confidence: 99%